2012
DOI: 10.1021/ol3007925
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Mediated Prevention of Aspartimide Formation in Solid Phase Peptide Synthesis

Abstract: Aspartimide formation is one of the major obstacles that impedes the solid phase synthesis of large peptides and proteins. Until now, no cost-effective strategy to suppress this side reaction has been developed. Here it is demonstrated that addition of small amounts of organic acids to the standard Fmoc cleavage agent piperidine efficiently prevents formation of aspartimide side products. This effect is shown to be virtually independent of the acid strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 20 publications
3
59
0
Order By: Relevance
“…24,25 Although N-hydroxylamine derivatives such as HOBt are known to be effective as buffers, we found it particularly economical to use formic acid, as reported by Mier. 26 Changing the deprotection solution from 80/20 DMF/piperidine to 80/19/1 DMF/piperidine/HCOOH for all deblock steps following aspartate incorporation, aspartimide formation was prevented without any obvious decrease in Fmoc deprotection efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…24,25 Although N-hydroxylamine derivatives such as HOBt are known to be effective as buffers, we found it particularly economical to use formic acid, as reported by Mier. 26 Changing the deprotection solution from 80/20 DMF/piperidine to 80/19/1 DMF/piperidine/HCOOH for all deblock steps following aspartate incorporation, aspartimide formation was prevented without any obvious decrease in Fmoc deprotection efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Since deprotection by hydrolysis in basic conditions led to aspartimide formation and resulted in a mixture of both the carboxylic acid ( 15 ) and primary amide side chain ( 14 b ), addition of formic acid (1.4 equiv., 0.2 equiv. with respect to LiOH) was mandatory to avoid this side reaction 25…”
Section: Resultsmentioning
confidence: 99%
“…Using microwave-SPPS and piperazine (5% piperazine with 0.1 M HOBt in DMF), the amount of aspartimide by-products observed during the synthesis of H-VYWTSPFMKLIHEQCNRADG-NH 2 was reduced from 32% to 3% [58]. More recently, it was demonstrated that the addition of Oxyma [77] and acids such as formic acid [78] to the Fmoc cleavage solution could also suppress the formation of aspartimide by-products. For example, in the presence of formic acid (5 vol.% to piperidine), aspartimide formation , was reduced by around 90% [78].…”
Section: Methods For the Synthesis Of Long/difficult Peptidesmentioning
confidence: 99%
“…More recently, it was demonstrated that the addition of Oxyma [77] and acids such as formic acid [78] to the Fmoc cleavage solution could also suppress the formation of aspartimide by-products. For example, in the presence of formic acid (5 vol.% to piperidine), aspartimide formation , was reduced by around 90% [78].…”
Section: Methods For the Synthesis Of Long/difficult Peptidesmentioning
confidence: 99%